I am Pilgrim : a thriller - Hayes, Terry, 1951- (New York : Emily Bestler Books, Atria, 2014)
Traces a collision between two geniuses--a tortured hero and a determined terrorist--in the aftermath of a murder that a world-class secret agent discovers has been conducted according to his own forensic techniques to hide the victim's identity.
Keywords: Intelligence officers -- Fiction; Terrorism -- Fiction; Suspense fiction